Branding about Indonesia through cross-cultural communication - Yunus, Ulani; Wahyuningtyas, Bhernadetta Pravita; Willyarto, Mario Nugroho (Jurnal Studi Komunikasi, 2020)
One of the most discussed issues currently is the competition of people among nations. Cross-cultural communication is becoming more and more apparent in countries in various aspects of life. This study aimed to provide an overview of how branding on Indonesia could be done through cross-cultural communication. The study examined cross-cultural communication between lecturers of Bina Nusantara University (Binus University) in Indonesia and lecturers from the Appalachian State University (ASU) the United States, as part of their research into Asian countries. The American lecturers interacted with lecturers from Binus University, Jakarta, as well as with the community in several regions of Indonesia. The study used a qualitative approach with descriptive method. This research was a case study with open interviews and observation of data collection techniques. The results showed that the interaction between Indonesian and American lecturers had built positive branding for Indonesia as reflected in posts on the American lecturers’ social media accounts which they did on their initiative after they visited Indonesia.